2022
DOI: 10.1007/s00059-022-05124-8
|View full text |Cite
|
Sign up to set email alerts
|

The future of heart failure with preserved ejection fraction

Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) is a multi-organ, systemic syndrome that involves multiple cardiac and extracardiac pathophysiologic abnormalities. Because HFpEF is a heterogeneous syndrome and resistant to a “one-size-fits-all” approach it has proven to be very difficult to treat. For this reason, several research groups have been working on methods for classifying HFpEF and testing targeted therapeutics for the HFpEF subtypes identified. Apart from conventional classification stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…These results together with the negative results of clinical trials targeting the NO/cGMP pathway weakens Paulus et al paradigm 5 and suggest that neither endothelial dysfunction nor cardiac inflammation is causing HFpEF . However, considering HFpEF is an heterogeneous disease with multiple pheno-groups 28 , these results needs to be verified in other animal models of HFpEF. Indeed, even though endothelial dysfunction does not seem to be necessary for diastolic dysfunction to develop upon a HFD + L-NAME regimen, EC protection was previously shown to prevent the occurrence of both diastolic and systolic dysfunction in other setting including pressure overload and hypertension 11 .…”
Section: Discussionmentioning
confidence: 99%
“…These results together with the negative results of clinical trials targeting the NO/cGMP pathway weakens Paulus et al paradigm 5 and suggest that neither endothelial dysfunction nor cardiac inflammation is causing HFpEF . However, considering HFpEF is an heterogeneous disease with multiple pheno-groups 28 , these results needs to be verified in other animal models of HFpEF. Indeed, even though endothelial dysfunction does not seem to be necessary for diastolic dysfunction to develop upon a HFD + L-NAME regimen, EC protection was previously shown to prevent the occurrence of both diastolic and systolic dysfunction in other setting including pressure overload and hypertension 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Modern research shows that the transition from HFpEF to HFrEF is rare. Compared with HFrEF, HFpEF has higher comorbidity and noncardiovascular mortality ( Heinzel and Shah, 2022 ). Therefore, the guide proposes different management models for HFpEF and HFrEF.…”
Section: Management Strategies For Hfpefmentioning
confidence: 99%
“…Recent studies have shown that myocardial injury in HFpEF is not primary but rather systemic inflammation caused by arterial hypertension or metabolic diseases such as diabetes and obesity. It eventually leads to coronary artery microvascular inflammation, dysfunction, subendocardial ischaemia, myocardial cellular mechanisms and metabolic changes ( Heinzel and Shah, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lab tests DBP, SBP and SVR are considered as risk factors imperative in HF prognosis 33 and are routinely monitored as part of the EHR, so the good results are not surprising. The HF cohort predominantly consists of older patients (e.g., 74 was the most prevalent age in our ACEI cohort), who are also more likely to have multiple comorbidities 34 , such as hypertension, diabetes mellitus, atrial fibrillation, and hyperlipidemia, which further contribute to the heterogeneity of HF 35 . So, using the Comorbidity information is beneficial as indicated by its satisfactory performance and identifying the combinations of the comorbidities corresponding to the different phenogroups as a next step could lead to targeted HF treatment.…”
Section: Part 1 Evaluationmentioning
confidence: 99%